2010
DOI: 10.1176/appi.ajp.2009.07081221
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Long-Acting Injection: A 24-Week, Randomized, Double-Blind Trial of Maintenance Treatment in Patients With Schizophrenia

Abstract: Olanzapine long-acting injection was efficacious in maintenance treatment of schizophrenia for up to 24 weeks, with a safety profile similar to oral olanzapine except for injection-related adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
166
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 179 publications
(179 citation statements)
references
References 15 publications
9
166
0
4
Order By: Relevance
“…Hospitalization rates for both treatment arms were adjusted linearly to a common follow-up period of 11 months. Kane et al 26 reported risk ratios based on exacerbation rates that include both rehospitalization and relapse. Risk ratios for the long-acting treatment arm were computed as a weighted average of the number of patients in the "very low" (n = 144), "low" (n = 140), "medium" (n = 318), and "high" (n = 141) dosage treatment arms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hospitalization rates for both treatment arms were adjusted linearly to a common follow-up period of 11 months. Kane et al 26 reported risk ratios based on exacerbation rates that include both rehospitalization and relapse. Risk ratios for the long-acting treatment arm were computed as a weighted average of the number of patients in the "very low" (n = 144), "low" (n = 140), "medium" (n = 318), and "high" (n = 141) dosage treatment arms.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusive answers about treatment effectiveness require both methodological rigor in comparing treatment outcomes and 26 were recalculated omitting the patients receiving very low dose long-acting olanzapine. b Depot-oral comparisons in which all-cause discontinuation was the primary endpoint (see Table 2) were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations